Erratum to: Does Adding Transdermal Nitroglycerine to Other Therapies Used for Management of Left-sided Congestive Heart Failure in Dogs Speed the Resolution of Clinical Signs? - Stillion, Jenefer R; Boysen, Søren R (Veterinary Evidence, 2018)
Unfortunately the original version of the article had the following two errors.